Structural analysis of the Louisburgh-Clare island succession, Co. Mayo, Ireland - Casini, G.; Ryan, P. D. (TRABAJOS DE GEOLOGÍA, 2009)
The Late Silurian Louisburgh-Clare Island Succession, south Co. Mayo, Ireland, is located along the Irish tract of the Highland Boundary Fault. This lineament originated in Ordovician times and was reactivated during Late Silurian-Middle Devonian times. Detailed structural analysis of the succession in the section between Turlin Strand and Shlivagh Rocks, south Clew Bay, was performed in order to determine the style and timing of deformation of the Silurian basin. The Louisburgh-Clare Island Succession recorded N-S contraction overprinted by roughly E-W oblique deformations. N-S contraction of the basin probably began before the end of Silurian deposition during pure shear dominated transpressional deformation and was replaced by dominant E-W transtensional deformation in Early/Middle Devonian time.